THE IMPACT OF FATHER’S ROLE TOWARDS ADOLESCENT SELFAWARENESS - Khasanah, Nurul; Safitri Harahap, Amelia; Hastuti Handayani, Sri; Oktaviani, Desy (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, criminal cases committed by adolescents are increasing trend The criminal cases, involving teenagers are now also suspected of misbehavior at school. To avoid this, teenagers need the ability to know themselves, know what to do, know their weaknesses and strengths that are owned or called self-awareness, where the role of fathers is one of the factors that influence self-awareness. The purpose of this research is to determine the effect of the role of fathers on self-awareness in teenager. This is a quantitative causal-comparative research. Subjects in this research were 100 teenagers taken by purposive sampling technique. The instrument used was a measure of the Role of the Father, totaling 43 valid items with reliability quality value of (α) = 0.959 and measuring the scale of self-awareness totaling 17 valid items with reliability value of (α) = 0.868. Regression test results mean that there is an influence of the role of fathers on self-awareness with sig. (p) 0,000; ((p)